The Effect of Interprofessional Collaboration and Total Quality Management on the Implementation of Electronic Medical Records In Outpatient Units Mediated By Work Culture - Lazuardy, Achmad Sirri; Andry; Markam, Hosizah (Al Makki Publisher, 2024)
The enactment of government regulations requires every health service facility to maintain electronic medical records as an effort to improve the quality of health services in Indonesia. There are 13,372 healthcare facilities in Indonesia and only 40% have run EMR. Influencing aspects: human data sources, policies, regulations, infrastructure and costs. There are still differences in aspects and responses of doctors and nurses to the implementation of electronic medical records. The importance of interprofessional collaboration through communication, joint decision making, coordination and cooperation, as well as continuous quality improvement through total quality management strategies and work culture of health workers as an effort to improve the quality of health services. The purpose of the study was to analyze the effect of interprofessional collaboration, total quality management on the implementation of electronic medical records in the mediation of work culture simultaneously and partially. The method uses descriptive statistics, quantitative associative correlations and questionnaires. Sampling using systematic random sampling from respondents of 109 health workers in the outpatient installation of RSUD Kabupaten Tangerang. The results showed that there is an influence of interprofessional collaboration and total quality management on the implementation of electronic medical records mediated by work culture. The coefficient value of the determination of influence on work culture variables and the implementation of electronic medical records of more than 0.75 is included in the medium category. Workshops related to the implementation of electronic edis records and effective communication among interprofessionals need to be conducted and further research can be carried out on the impact and benefits.